Recovery from COVID-19 in a B-cell-depleted multiple sclerosis patient. (September 2020) - Wurm, Hannah; Attfield, Kate; Iversen, Astrid KN; Gold, Ralf; Fugger, Lars; Haghikia, Aiden
Approximately 200, 000 multiple sclerosis (MS) patients worldwide receive B-cell-depleting immunotherapy with rituximab (anti-CD20), which eliminates the ability to generate an antibody response to new infections. As severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–specific antibodies might help viral clearance, these patients could be at risk of severe complications if infected. Here, we report on an MS patient who had received rituximab for ~3 years. The patient was examined 5 days before the onset of coronavirus disease 2019 (COVID-19) symptoms and was admitted to the hospital 2 days after. She recovered 14 days after symptom onset despite having a 0% B lymphocyte count and not developing SARS-CoV-2 immunoglobulin G (IgG) antibodies.